2018
DOI: 10.3389/fpsyg.2018.01085
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Assessment of Older Adults With Virtual Reality: Association of Age, Schooling, and General Cognitive Status

Abstract: The development of neuropsychological assessment methods using virtual reality (VR) is a valid and promising option for the detection of cognitive impairment in the older people, focusing on activities composed of tasks of multiple demands. This study verified the association of age, schooling, and general cognitive status on the performance of neurologically healthy older adults in ECO-VR, a VR task of multiple demands for neuropsychological assessment. A total of 111 older adults answered a sociodemographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(59 reference statements)
3
10
0
Order By: Relevance
“…In addition, although the MMSE has a modest specificity for screening MCI, its sensitivity for screening MCI is low, and the capacity to detect MCI converters is poor [ 28 ]. This outcome is consistent with that of Oliveira et al, who also showed a weak correlation between MMSE scores and performance in VR research [ 39 ]. Chan et al [ 45 ] and Chua et al [ 37 ] also conducted correlation analyses with MoCA scores when verifying the screening application for MCI, which they had developed, and showed strong correlations between the measures.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, although the MMSE has a modest specificity for screening MCI, its sensitivity for screening MCI is low, and the capacity to detect MCI converters is poor [ 28 ]. This outcome is consistent with that of Oliveira et al, who also showed a weak correlation between MMSE scores and performance in VR research [ 39 ]. Chan et al [ 45 ] and Chua et al [ 37 ] also conducted correlation analyses with MoCA scores when verifying the screening application for MCI, which they had developed, and showed strong correlations between the measures.…”
Section: Discussionsupporting
confidence: 93%
“…VSP scores were negatively correlated with age, which is consistent with the work of Chua et al [ 37 , 39 ]. Considered a task involving multiple demands, the VSP was formed by a series of activities consisting of goals during its execution, and it requires activation and cooperation of multiple cognitive domains [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As VR technology advances and related research accumulates, obstacles that blocked the application of VR neuropsychological tests to the elderly are being resolved [ 97 ]. Figure 7 also shows the expansion of the research to the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…If so, it seems imperative to examine how it affects our cognition. Furthermore, based on the assumption that the brain is plastic and adaptable, some alterations and changes are expected to optimize resources or even compensations by improving other skills (Oliveira et al, 2018 ; Bubbico et al, 2020 ; Della Gatta et al, 2021 ).…”
mentioning
confidence: 99%